Designing a User-Centered Smart Wound Consultation Model for Smartphone-Based Wound Care - Mardiana Mochamad Ramdan; Fitri Nurlina; Mochamad Budi Santoso; Heri Budiawan; Miftahu Falah (HealthCare Nursing Journal, 2026)
Wound care faces increasing challenges due to the growing prevalence of chronic wounds, limited access to wound care specialists, and the need for continuous healthcare services. Smartphone technology provides opportunities to improve access to integrated wound consultation. This study aimed to develop a user-centered smartphone-based Smart Wound Consultation model, identify its essential features, and establish a workflow for wound consultation and digital documentation. A Design Science Research approach with user-centered design principles was employed. The study was conducted in Tasikmalaya, Indonesia, involving four purposively selected experts in information technology, medical-surgical nursing, and wound care. Data were collected through expert discussions and design validation forms and analyzed using thematic analysis. The proposed model integrates six core features: wound screening, medication services, self-care support, homecare services, health education, and educational videos within a single smartphone platform. The workflow includes initial wound assessment, telenursing consultation, treatment recommendations, digital documentation, and referral pathways. Expert validation confirmed the feasibility of the model following minor revisions to medical terminology, screening content, educational materials, and referral mechanisms. The proposed model provides a comprehensive user-centered framework for digital wound consultation and offers a foundation for developing smartphone-based applications to improve access, continuity, and quality of Medical-Surgical Nursing services.